2006
DOI: 10.1111/j.1365-2443.2006.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Rho GTPase‐activating protein RICS in neurite outgrowth

Abstract: The Rho family of small GTPases, including RhoA, Rac1 and Cdc42, are critical regulators of the actin cytoskeleton. In neuronal systems, Rho GTPase-activating proteins (RhoGAPs) and their substrates, Rho GTPases, have been implicated in regulating multiple processes in the morphological development of neurons, including axonal growth and guidance, dendritic elaboration and formation of synapses. RICS is mainly expressed in the brain and functions as a RhoGAP protein for Cdc42 and Rac1 in vitro . To examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 26 publications
0
32
1
2
Order By: Relevance
“…We focused on p250GAP because it was the only predicted miR132 target that showed perfect conservation across the vertebrate phylum. In vivo pull-down assays suggest that p250GAP potentially regulates several Rho family GTPases (16)(17)(18)(19)(20), and cerebellar granule cells from p250GAP-knockout mice show increased Cdc42 activity (18). p250GAP is enriched in the postsynaptic density where it interacts with the NMDA NR2B receptor subunit and the scaffold protein PSD-95 (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on p250GAP because it was the only predicted miR132 target that showed perfect conservation across the vertebrate phylum. In vivo pull-down assays suggest that p250GAP potentially regulates several Rho family GTPases (16)(17)(18)(19)(20), and cerebellar granule cells from p250GAP-knockout mice show increased Cdc42 activity (18). p250GAP is enriched in the postsynaptic density where it interacts with the NMDA NR2B receptor subunit and the scaffold protein PSD-95 (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…p250GAP has been reported to inhibit Rho family GTPases in vitro (16)(17)(18)(19)(20). To determine which Rho family GTPases participate in miR132-and p250GAP-regulated dendritic growth, we used dominant-interfering mutants.…”
Section: Activity Regulates Dendritic Growth Via Mir132 Inhibition Ofmentioning
confidence: 99%
“…RICS is expressed predominantly in neurons of the brain and involved in neurite extension at the growth cones and presumably N-methyl-D-aspartate (NMDA) signaling at the post-synaptic density (PSD), where it forms a complex with ␤-catenin, N-cadherin, NMDA receptors, and PSD-95 Nasu-Nishimura et al 2006). Recently, we identified a splicing variant of RICS, termed PX-RICS, which is expressed in a wide variety of tissues and cell lines (Hayashi et al 2007).…”
mentioning
confidence: 99%
“…Coomassie Blue staining shows the GST fusions used in the pull-down assay. studies of p200 in mice suggest that deletion of p200 causes an up-regulation of Cdc42 activity in the neuron (35). Under overexpression conditions in NIH 3T3 cells, we found that p200 was an active GAP in down-regulating RhoA-GTP and Cdc42-GTP formation, whereas p200 R58K was inactive toward Cdc42 or RhoA (Fig.…”
Section: P200 Rhogap-induced Cellular Transformation Requires Both Thmentioning
confidence: 74%